Faecal immunochemical test-based colorectal cancer screening in Mexico: an initial experience. (21st January 2020) - Remes-Troche, José María; Hinojosa-Garza, Gabriela; Espinosa-Tamez, Priscilla; Meixueiro-Daza, Arturo; Grube-Pagola, Peter; Van Loon, Katherine; Potter, Michael B; Lajous, Martin
Abstract: Background: In middle-income countries, the burden of colorectal cancer (CRC) is increasing in parallel with resources for diagnosis and treatment. There is a potential benefit of CRC screening programs in Mexico. Objective: Since there are no organized screening programs in the country, we explored the willingness of individuals to complete a faecal immunochemical testing (FIT) based CRC screening program and its potential benefit in Mexico. Methods: We conducted a CRC screening program pilot in Veracruz, Mexico, during 2015–16 using FIT. Individuals with FIT results >100 ng of haemoglobin/ml buffer were referred for diagnostic colonoscopy. Results: Of 473 FIT kits distributed to adults aged 50–75, 85.8% (406) were completed by participants and analysed in the laboratory. Of these, 5.9% (24/406) of test results showed >100 ng haemoglobin/ml. Twenty-one participants completed colonoscopy. The positive predictive value of FIT >100 ng haemoglobin/ml for premalignant lesions was 33%. Conclusion: These results provide preliminary evidence of the willingness of individuals to complete FIT-based CRC screening program in Mexico. However, further evaluation of health systems resources will be needed prior to large-scale implementation of CRC screening programs.